2017
DOI: 10.1007/s12035-017-0486-6
|View full text |Cite
|
Sign up to set email alerts
|

N-Propargyl Caffeamide (PACA) Ameliorates Dopaminergic Neuronal Loss and Motor Dysfunctions in MPTP Mouse Model of Parkinson’s Disease and in MPP+-Induced Neurons via Promoting the Conversion of proNGF to NGF

Abstract: Insufficient production of nerve growth factor (NGF) is implicated in Parkinson's disease (PD). We recently discovered that caffeic acid derivative N-propargyl caffeamide (PACA) not only potentiated NGF-induced neurite outgrowth but also attenuated 6-hydroxydopamine neurotoxicity in neuronal culture. The aim of the present study was to investigate whether PACA could increase NGF levels against 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) neurotoxicity in a mouse PD model. We induced parkinsonism in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
(58 reference statements)
0
27
0
Order By: Relevance
“…Additionally, the results from a genome-wide association study demonstrated that CREB interacting with some of risk genes of mental disorders, suggesting that CREB probably be identified as one of the risk factors for psychiatric disorders including schizophrenia and major depression disorder [62]. Besides, enhancement of p-ERK/p-CREB signaling ameliorated the death of dopaminergic cell line SH-SY5Y cells after neurotoxin MPP + challenge and dopaminergic neurons in substantia nigra (SN) by neurotoxin MPTP treatment [40,63]. Together, these findings revealed that cAMP-calcium-ERK-CREB signaling was a very important regulator of neurological disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the results from a genome-wide association study demonstrated that CREB interacting with some of risk genes of mental disorders, suggesting that CREB probably be identified as one of the risk factors for psychiatric disorders including schizophrenia and major depression disorder [62]. Besides, enhancement of p-ERK/p-CREB signaling ameliorated the death of dopaminergic cell line SH-SY5Y cells after neurotoxin MPP + challenge and dopaminergic neurons in substantia nigra (SN) by neurotoxin MPTP treatment [40,63]. Together, these findings revealed that cAMP-calcium-ERK-CREB signaling was a very important regulator of neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…As one member of mitogen-activated protein kinases (MAPK) family, extracellular signal-related kinase (ERK) plays vital roles in cell migration, cell proliferation, cell differentiation and apoptosis [39]. Early studies showed that enhancement of p-ERK protected dopaminergic neurons in substantia nigra from death caused by neurotoxin MPTP [40], indicating the important role of ERK in brain disorders. Moreover, previous research demonstrated that both 5-HT1AR and OX2R regulated the levels of [15,20].…”
Section: -Ht1ar-ox2r Heterodimer Downregulated P-erk Levelsmentioning
confidence: 99%
“…Mice were evaluated for motor impairments with a rotarod apparatus (Harvard apparatus, Holliston, MA, USA) as described [ 26 , 27 ]. In brief, at 3 days after last dosage of MPTP treatment, mice were subjected to behavioral assessments.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of TH in the midbrain was detected by immunohistochemical staining as previously described [ 27 ]. In brief, mice were transcardially perfused sequentially with saline and 4% paraformaldehyde under anesthetic condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation